2014
DOI: 10.1002/smi.2615
|View full text |Cite
|
Sign up to set email alerts
|

Positive Psychological Factors are Associated with Lower PTSD Symptoms among Police Officers: Post Hurricane Katrina

Abstract: Following Hurricane Katrina, police officers in the New Orleans geographic area faced a number of challenges. This cross-sectional study examined the association between resilience, satisfaction with life, gratitude, posttraumatic growth, and symptoms of posttraumatic stress disorder in 84 male and 30 female police officers from Louisiana. Protective factors were measured using the Connor–Davidson Resilience scale, Satisfaction with Life Scale, the Gratitude Questionnaire, and the Posttraumatic Growth inventor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 56 publications
(115 reference statements)
7
114
1
4
Order By: Relevance
“…Research has identified a number of protective factors, which can mitigate the risk for PTSD, such as resilience, satisfaction with life, gratitude and positive coping skills (McCanlies et al ., ). Some officers are able to exhibit post‐traumatic growth in response to stressors (Chopko, Palmieri, & Adams, ).…”
Section: Post‐traumatic Stress Disordermentioning
confidence: 99%
“…Research has identified a number of protective factors, which can mitigate the risk for PTSD, such as resilience, satisfaction with life, gratitude and positive coping skills (McCanlies et al ., ). Some officers are able to exhibit post‐traumatic growth in response to stressors (Chopko, Palmieri, & Adams, ).…”
Section: Post‐traumatic Stress Disordermentioning
confidence: 99%
“…The development of PTSD is dependent on several dynamics. Certain factors such as social support subsequent to the trauma, individual resiliency, and post-trauma growth have been found reduce the risk of PTSD (Andrew et al 2013; McCanlies et al 2014; Paton and Norris 2014; Tedeschi and Calhoun 1996; Violanti 2014). Post-trauma growth describes a positive change that occurs in one’s life following a traumatic event (Lindstrom etal.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, peritraumatic experiences, prior trauma, and multiple traumatic experiences have been found to exacerbate PTSD risk (Marmar et al 2006; McCanlies et al 2014). PTSD rates in officers have been reported to be as low as 7% and as high as 19% (Carlier et al 1997; Maia et al 2007; Schutte et al 2012; Violanti 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Protective factors, such as social support, resiliency, gratitude and satisfaction with life have been shown in prior studies to be associated with fewer PTSD symptoms (Andrew et al ., 2014; McCanlies, Mnatsakanova, Andrew, Burchfiel, and Violanti, 2014; Paton and Norris 2014). Conversely, exposure to prior trauma, maladaptive coping styles, and low neurocognitive abilities have been associated with increased risk of PTSD (Marmar et al ., 2006; DiGangi et al ., 2013).…”
Section: Ptsdmentioning
confidence: 99%